KEBERADAAN KAPANG PENGKONTAMINASI KULIT MANIS (Cinnamomum burmanii. Bl) YANG DIJUAL DI PASAR RAYA KOTA PADANG - Fitria, Dila; Fifendy, Mades; Nurmiati, Nurmiati (STKIP PGRI Sumbar, 2013)
ABSTRACTCassia in says to curry nice constitutes one of plant which be utilized as raw material of allspice and constitutes Indonesian export commodity that adequately is of important. In drying up process usually curries nice be basked then nice skin furls, openair nice skin was temporary dry that in roll is still damp in here can wooded fungoid microorganism. Processing and laid up that done by ala not good will be easily to attack pest and also being at repository. To the effect this research is subject to be know mold type existences pengkontaminasi curries nice that is sold at Market. This research utilize surveys method at field with tech Simple Random Sampling. Isolating result to be done descriptive watch with insulate mould of nice skin, making pure breeding, then does identification until species zoom. 8 found observational result pengkontaminasis mould type curries nice that is sold at Market. Found mold type is Aspergillus is niger, Aspergillus sp1. predicted Aspergillus oryzae, Aspergillus sp2. predicted Aspergillus fumigatus , Mucor sp, Penicillium sp1., Penicillium sp2., Penicillium sp3., Penicillium sp4. Conclusion on skinned nice one is sold at Market terkontaminasi by mold.